Analysis of Regional Expenditure Efficiency in the Management of the Tuban Regency Budget During the Covid 19 Pandemic - Kevin Raditya Kusuma; Satria Wahyu Helmyawan; Eva Hany Fanida; Melda Fadiyah Hidayat (Pustaka Digital Indonesia, 2026)
The Covid-19 pandemic has caused great fiscal pressure for local governments, including Tuban Regency. Local governments are required to maintain public services while adjusting spending priorities through budget refocusing and reallocating policies. This study aims to analyze the efficiency of regional spending in the management of the Regional Revenue and Expenditure Budget (APBD) of Tuban Regency during the pandemic period of 2020–2021. The research uses a descriptive quantitative approach with secondary data in the form of the Tuban Regency Government Budget Realization Report for 2020 and 2021. The analysis technique used is the expenditure efficiency ratio, which is the comparison between the realization of expenditure and the expenditure budget. The results of the study show that the expenditure efficiency ratio in 2020 was 87.05% and in 2021 was 85.07%, with an average of 86.06%. Based on the criteria used, the two years are included in the category of being very efficient. These findings show that the Tuban Regency Government is able to control the realization of spending that remains below the budget set during the pandemic. This condition reflects the adaptive capacity of local governments in managing regional finances through adjusting spending priorities and strengthening fiscal discipline during times of crisis.